Bullying Prevention Management Based on Child-Friendly Schools at SD Muhammadiyah Bayen Sleman - Muntasiyah Muntasiyah; Sukirman Sukirman; Suyatno Suyatno (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Bullying in elementary schools remains a persistent threat to children's psychological safety and academic development, yet most empirical studies on school-based bullying prevention have concentrated on secular public schools or on isolated interventions such as classroom counseling, peer-mediation programs, or single-shot anti-bullying campaigns. This study addresses that gap by examining how child-friendly, school-based management for bullying prevention is implemented at SD Muhammadiyah Bayen Sleman. The researcher employed a qualitative research design with a case study approach. Data collection was conducted through semi-structured interviews, and the collected data were analyzed using thematic analysis. The findings show that the school operationalizes a four-stage cycle, planning (hotspot mapping and a shared operational definition of bullying), organizing (formation of an anti-bullying team and expert-led training), implementing (curriculum integration across all subjects, not only guidance counseling, and habituation of Islamic character values), and controlling (periodic, collaborative evaluation). The results contribute a context-specific model of faith-integrated bullying prevention management that can inform both theory (by showing how religious values function as an integrating mechanism across management functions, rather than as a separate variable) and practice (by offering other schools, religious or secular, a replicable four-function cycle for building a child-friendly, bullying-free environment)